The role of salt stress on laboratory cultivation of green macroalga Enteromorpha compressa and its antioxidant activity (Baghdad Science Journal, 2021)
Cultivation of the green seaweed Enteromorpha compressa was performed under natural laboratory spring environmental conditions of temperature, light intensity and photoperiod to study the salinity tolerance of this intertidal green macroalga. Cultivation was carried out under artificial seawater (ASW) of different concentrations (18, 35, 53 and 106 g/l sea salt) compared to the control using natural seawater (NSW). Growth rate and pigment content of the cultivated alga were recorded at regular intervals during the experimental duration. Antioxidant activity of the crude ethanolic extract and its fractions (petroleum ether, chloroform, ethyl acetate and acetone) was performed against DPPH radical scavenging assay and compared to the standard synthetic antioxidant butylated hydroxy-toluene (BHT). The finding showed that enhancement of algal growth rate under ASW concentrations of 35, 53 and to a lesser extent at 106 g/L during the first 15 days of cultivation were due to the increased pigment biosynthesis, photosynthetic and metabolic activities and followed by gradual retardation due to the impact of prolonged salt stress. Antioxidant activity of alga was found to be concentration, type of extract and incubation time dependent. Acetone fraction of all salt concentrations showed higher antioxidant activity compared to other fractions. Pronounced activity was recorded at higher seawater conc. (106g/l).